CRITICAL DOSE OF NITROGEN AND PHOSPHORUS FOR THE ENHANCED GROWTH, YIELD, AND QUALITY COMPONENTS IN MUSTARD (Sinapsis arvensis L.) IN A SEMI ARID ENVIRONMENT - Erim, Esengul; Sefaoglu, Firat; Toktay, Zehra; Öztürk, Erdoğan (Turkish Journal of Field Crops, 2021)
Mustard grows in many parts of the world thanks to its ability to adapt to different climatic conditions. It has the potential to be an important oilseed plant especially in the east of Turkey. There is scarcely any information available about fertilization in mustard cultivation in Turkey. Nitrogen and phosphorus fertilizers, a good source of nutrients for the soil, have a positive effect on the growth, development, and yield of the plant in case they are applied at the optimum level. This study was carried out in 2015 and 2016 with the purpose of examining the effects of nitrogen and phosphorus fertilization on the yield and agronomic characteristics of mustard. Five doses of nitrogen (0, 50, 100, 150, 200 kg ha-1) and phosphorus (0, 30, 60, 90, 120 kg ha-1) were tested. It was found that the nitrogen and phosphorus applications had significant effects on the plant growth, yield, and yield components in both 2015 and 2016. The characteristics examined within the scope of the study were significantly affected by the applications, and the oil content and seed yield increased with the increasing fertilizer doses. The results of the study emphasize the importance of fertilizer applications for the mustard plants grown in semi-arid climates. 200 kg ha-1 of nitrogen and 120 kg ha-1 of phosphorus were found to yield better results, and it was observed that the seed yield of mustard could be increased by increasing the doses of nitrogen and phosphorus.
Keywords: Mustard; nitrogen use efficiency; optimum fertilizer dose; fertilization; Agronomy; Agronomi; 2. Zero hunger; 15. Life on land